Capturing diversity and cultural drivers of food choice in eastern India - Samaddar, Arindam; Cuevas, Rosa Paula; Custodio, Marie Claire; Ynion, Jhoanne; Ray (Chakravarti), Anindita; Mohanty, Suva Kanta; Demont, Matty (Elsevier, 2020)
The EAT-Lancet Commission urgently called for “planetary health diets”. The success of encouraging dietary shifts, however, crucially hinges on people, and more specifically on consumers' culture, context, socioeconomic status, food environment, attitudes, perceptions, beliefs, and behavior towards food choice. In India, enhanced food availability and accessibility do not readily lead to improved nutritional status. Thus, developing planetary health diets in India requires an understanding of systemic drivers of food choice. Food is an essential part of Indian culture and deeply rooted to the country's history, traditions, lifestyles, and customs. Yet, the diversity and cultural drivers of food choice are still insufficiently understood. To address this knowledge gap, we use expert elicitation to contextualize the “gastronomic systems research” framework to a target population of low-to middle-income households to capture the diversity and cultural drivers of food choice and its nutritional implications in rice-based diets in two states in eastern India. The experts catalogued 131 unique dishes associated with five differentiated daily dining occasions. The majority of dishes belong to the starch food group. Morning snacks exhibit the lowest nutritional diversity while dinners feature the highest diversity in both states. In West Bengal, dish options tend to be carbohydrate-rich and energy-dense, and a significant number of dishes are fried and oily. The gastronomic system mapped by the experts provides a useful baseline for nutritionists, policymakers, and food system actors as a first step in the design of nutrition intervention strategies to develop planetary health diets in eastern India.